2021
DOI: 10.1159/000514562
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Acute Ischemic Strokes in Patients with COVID-19

Abstract: <b><i>Introduction:</i></b> Acute ischemic stroke (AIS) and thrombotic events (TEs) were reported in patients with COVID-19. Clinical outcome of AIS in the course of COVID-19 remains unknown. We compared early clinical outcome and mortality of COVID-positive (+) patients admitted for AIS with COVID-negative (−) ones. We hypothesized that COVID+ patients would have poorer clinical outcomes and present a higher rate of TEs and mortality compared with COVID− ones. <b><i>Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
1
11
0
2
Order By: Relevance
“…We observed twice higher inhospital and 3-month mortality in patients hospitalized for stroke with a primary diagnosis of COVID-19 (group B). This result might highlight the difficulty to manage patients with both acute stroke and severe COVID-19 in terms of care pathway organization including prehospital management, emergency department regulation, interhospital transfers, and endovascular procedures as found in previous studies [8,9] from France [10], the stroke care network of Madrid [11], in Germany [4], in Lombardy and Italy [12]. These difficulties led to the publication of a guidance statement based on shared best practices in May 2020 [13].…”
Section: Discussionmentioning
confidence: 75%
“…We observed twice higher inhospital and 3-month mortality in patients hospitalized for stroke with a primary diagnosis of COVID-19 (group B). This result might highlight the difficulty to manage patients with both acute stroke and severe COVID-19 in terms of care pathway organization including prehospital management, emergency department regulation, interhospital transfers, and endovascular procedures as found in previous studies [8,9] from France [10], the stroke care network of Madrid [11], in Germany [4], in Lombardy and Italy [12]. These difficulties led to the publication of a guidance statement based on shared best practices in May 2020 [13].…”
Section: Discussionmentioning
confidence: 75%
“…The median duration from COVID-19 symptom onset to stroke diagnosis across several studies was approximately 12–16 days (with a range of 5–28 days) [ 21 •, 40 , 41 ]. Several studies have shown that COVID-19 infection is associated with higher stroke severity, worse functional outcomes, and greater mortality [ 40 , 42 ].…”
Section: Pre-stroke Infection and Stroke Outcomesmentioning
confidence: 99%
“…The median duration from COVID-19 symptom onset to stroke diagnosis across several studies was approximately 12–16 days (with a range of 5–28 days) [ 21 •, 40 , 41 ]. Several studies have shown that COVID-19 infection is associated with higher stroke severity, worse functional outcomes, and greater mortality [ 40 , 42 ]. The clear temporal relationship between COVID-19 symptom onset and acute stroke symptom onset supports the notion that pre-stroke infection does indeed detrimentally impact outcomes after stroke.…”
Section: Pre-stroke Infection and Stroke Outcomesmentioning
confidence: 99%
“…However, more data is required to provide more robust evidence. Studies have shown that COVID-19 patients with acute ischemic stroke had a higher mortality rate [18], [19], [20]. Those who had ischemic stroke and COVID-19 had a higher rate of thrombotic events and a higher mortality rate (15% vs. 2.8%) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that COVID-19 patients with acute ischemic stroke had a higher mortality rate [18], [19], [20]. Those who had ischemic stroke and COVID-19 had a higher rate of thrombotic events and a higher mortality rate (15% vs. 2.8%) [18]. A multicenter study in Spain found that ischemic stroke patients with COVID-19 had a mortality rate up to 39.3% compared to 16.1% only among those without COVID-19 [19].…”
Section: Introductionmentioning
confidence: 99%